THE INFLUENCE OF STUDENTS' RELIGIOSITY ON FUJOSHI BEHAVIOR - yani, Meri; R, M. Dahlan; Nawawi, Kholil (Universitas Labuhanbatu, 2024)
Religiosity is a person's level of knowledge and understanding of the religion he adheres to. Therefore it is very important for students to have religiosity. But not a few students who have religiosity but still do things that are forbidden by Allah SWT. As is the case in today's era, namely the rise of shows or readings about homosexuality. In fact, the average perpetrators of reading and watching are teenagers who are students. This study aims to determine the effect of students' religiosity on fujoshi behavior. The method used in this research is a quantitative approach with a field research approach. This research was conducted at SMA Negeri 2 Bogor City from September 2022 to February 2023. The population consisted of 175 class X students and a sample of 45 was selected by means of probability. Data collection was carried out using a questionnaire totaling 30 items with a validity value of 0.850 and 0.000 as a result of normality. The results of the study show that the fujoshi performers are not affected by religiosity. This means that students who are still undergoing worship such as praying five times a day, fasting and reciting the Koran but cannot make students stop being fujoshi where they are still doing fujoshi behavior such as reading and watching boys love.Keywords: Religiosity, Learners, Fujoshi BehaviorAbstrakReligiosity is a person's level of knowledge and understanding of the religion they adhere to. Therefore, it is very important for students to have religiosity. However, there are quite a few students who have religiosity but still do things that are prohibited by Allah SWT. As is happening nowadays, namely the rise in viewing or reading about homosexuality. In fact, on average, the perpetrators of this reading and watching are teenagers who are students. This research aims to determine the influence of students' religiosity on fujoshi behavior. The method used in this research is a quantitative approach with a field study approach. This research was carried out at SMA Negeri 2 Bogor City from September 2022 to February 2023. The population was 175 class X female students and a sample of 45 was selected using probability. Data collection was carried out using a 30-item questionnaire with a validity value of 0.850 and 0.000 as a result of normality. The research results show that fujoshi practitioners are not influenced by religiosity. This means that students who still carry out religious services such as praying five times a day, fasting and reciting the Koran cannot make students stop being fujoshi, where they still carry out fujoshi behavior such as reading and watching boys love.Keywords: Religiosity , Students , Behavior Fujoshi